Cognitive, Behavioral and Emotional Empathy in Pharmacy Students: Targeting Programs for Curriculum Modification - Tamayo, Cassandra A.; Rizkalla, Mireille N.; Henderson, Kyle K. (Frontiers in Pharmacology, 2016)
Introduction: Empathy is an essential trait for pharmacists and is recognized as a core competency that can be developed in the classroom. There is a growing body of data regarding levels of empathy in pharmacy students; however, these studies have not measured differences in behavioral, cognitive, and emotional empathy. The goal of this study was to parse the underlying components of empathy and correlate them to psychosocial attributes, with the overall goal of identifying curriculum modifications to enhance levels of empathy in pharmacy students. Methods: IRB approval was obtained to measure empathy levels in pharmacy students attending Midwestern University. An online, anonymous survey administered through a secure website (REDCap) was used. This survey utilized the Jefferson Scale of Empathy (Medical Student version) and included questions regarding demographics and personality traits. Empathy questions were sub-divided into behavioral, cognitive, and emotional categories. Data are presented as mean ± SEM with significance set at P < 0.05. Results: Three hundred and four pharmacy students at Midwestern University participated in a fall survey with an overall response rate of 37%. The average empathy score was 110.4 ± 0.8 on a scale of 20-140; which is comparable to empathy scores found by Fjortoft et al. and Van Winkle et al. Validating prior research, females scored significantly higher than males in empathy as well as behavioral, cognitive, and emotional subcomponents. For the entire population, emotional empathy was significantly higher than cognitive and behavioral empathy (P < 0.05). Furthermore, negative correlations to empathy were observed for self-serving behavior (R = 0.490, P < 0.001), medical authoritarianism (R = 0.428, P < 0.001), and experience of coercion (R = 0.344, P < 0.001). Conclusion: Overall, empathy levels in pharmacy students are similar to prior studies with females scoring higher than males. Emotional empathy may play a greater role than cognitive and behavioral empathy in this group of students. Targeted programs that promote volunteerism and activities that foster responsiveness to patient needs may attenuate self-serving behavior and medical authoritarianism and, therefore, improve empathy levels in pharmacy students.